Effect of Yashtimadhu Ghrita Gudapurana on Post Operative Pain Management in Patients of Haemorrhoids and Fissure-in-ano with Special Reference to Shastranipataja Vedana: A Randomized Controlled Trial. (International Journal of Ayurveda and Pharma Research, 2022)
Modern medical Science has offered many surgical procedures like open and closed haemorrhoidectomy, anal dilatation, Sphincterotomy etc for haemorrhoides and fissure in ano. These operative procedures are associated with unavoidable sequel of symptoms like Pain, Discharge and Inflammation etc. Role of analgesia is vital in the treatment of post-operative pain. The mode of analgesia depends on degree or level of pain which is a subjective criteria. Analgesics routinely used are NSAIDs, opioids and corticosteroids. Side effects includes like Gastritis, Gastrointestinal bleeding etc. Hence, Analgesia has to be supplemented with antacids or H2 Receptor Agonists. Here, quest for knowledge for an alternative treatment to analgesics starts. According to Sushrutacharya, these diseases like Arsha and Parikartika are termed as Chhedya, i.e., treatable by surgery and he has indicated Yashtimadhu Ghrita in Shastranipataja Vedana. Methodology- In present study, total 100 postoperative patients of haemorrhoids and fissure in ano, randomly allocated into two groups (50 in each group). In Group A (n = 50), Yashtimadhu Ghrita Gudapurana was done every day after sitz bath for 5 days. In Group B (n = 50), local application of lignocaine jelly every day after sitz bath for 5 days. Result- Yashtimadhu Ghrita as a local application is clinically as effective as lignocaine jelly in the management of post operative pain in patients of hemorrhoids and fissures in ano. Conclusion- it was concluded that Yashtimadhu Ghrita is helpful in the management of pain in the post operative patient of haemorrhoids and fissure in ano